Modernization and Islamist Conflict - Daniel Meierrieks; Tim Krieger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This contribution studies the impact of modernization on the onset of Islamist conflict. To capture the multi-dimensional phenomenon of modernization, we create a unique modernization index. Our empirical analysis for 154 countries for the 1971-2006 period provides robust evidence that modernization rather than economic underdevelopment or a lack of democracy increases the likelihood of the onset of Islamist conflict. This relationship especially matters to Islamist groups that aim at a regime change, i.e., the establishment of an Islamic state, while separatist groups seem to be more strongly affected by minority discrimination. We argue that from a rational-economic point of view the adverse effects of modernization lower the opportunity costs of conflict and raise its benefits. Additionally, an Islamist framing of modernization grievances affects the cost-benefit considerations of potential Islamist militants in ways that make violence even more likely (e.g., by offering spiritual rewards). An Islamist interpretation of modernization grievances furthermore provides Islamist militants with a political objective (the establishment of an Islamic state) to remedy the perceived ills of modernization.
Keywords: D74; O10; Z12; 330